1999
DOI: 10.1007/s004310051012
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising enterocolitis: is there a relationship to specific pathogens?

Abstract: Although gut colonisation with potential pathogens appeared to be a prerequisite for the development of NEC, there were no specific bacteria associated with this disease if data from infants with NEC were compared with those from time- and gestational age-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 23 publications
(35 reference statements)
2
46
1
7
Order By: Relevance
“…Some studies have found an association between various bacterial species and NEC (15)(16)(17)(18)(19)(20), whereas others did not observe any association between NEC and any specific bacterial species (8,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found an association between various bacterial species and NEC (15)(16)(17)(18)(19)(20), whereas others did not observe any association between NEC and any specific bacterial species (8,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is suspected that abnormal colonization of the gastrointestinal tract or an unfavorable balance between commensal and pathogenic bacteria is part of the pathogenesis of NEC (4)(5)(6). It has been suggested that the ability of microflora to invade the epithelium and ferment unabsorbed nutrients (7), and the colonization by various bacterial pathogens in a sufficiently vulnerable host (8) could promote the development of NEC. Bacterial colonization of the neonatal gut is influenced by factors such as gestational age, feeding, medication, and diverse environmental flora (9).…”
mentioning
confidence: 99%
“…The pathogenesis of disease implies delayed gut colonisation with a limited number of bacterial species, which tend to be virulent (Dai & Walker, 1998). Although colonisation with potential pathogens appears to be a prerequisite for development of NEC, no speci®c bacteria have been associated with the condition (Peter et al 1999). Animal models of NEC have implicated Clostridium spp.…”
Section: Neonatal Necrotising Enterocolitismentioning
confidence: 99%
“…Additionally, studies in fetal and germ-free preterm pigs, and in quails, show that the initial bacterial colonization is a prerequisite for the development of NEC (5,53,68). Regardless, no specific pathogen has been identified as the primary cause of NEC (47,69) although bacterial overgrowth may be a key element in the etiology of NEC (37). Bacterial overgrowth may result from factors such as intestinal dysmotility, reduced digestive function, and immature immunological responses to microbial colonization, all of which are characteristics of the premature gut (3,37).…”
mentioning
confidence: 99%